Scale dependence of felid predation risk: identifying predictors of livestock kills by tiger and leopard in Bhutan - Rostro-García, S; Tharchen, L; Abade, L; Astaras, C; Cushman, S; Macdonald, D (Springer Netherlands, 2016)
Context: Livestock predation by tiger and leopard in Bhutan is a major threat to the conservation of these felids. Conflict mitigation planning would benefit from an improved understanding of the spatial pattern of livestock kills by the two predators. Objectives: We aimed to identify the landscape features that predict livestock kills by tiger and leopard throughout Bhutan. Our goals were to: (1) identify the predictors that have the largest influence in determining livestock kills, (2) assess the influence of scale across the different predictors evaluated and identify the scale at which each was most important. Methods: We used livestock kills obtained from compensation records of tiger (n = 326) and leopard (n = 377) across Bhutan between 2003 and 2012 to run predation risk models with MaxEnt algorithm, using a multi-scale modeling approach (1, 2, 4, 8 and 16 km). Results: Human-presence (density of settlements and roads) and land-cover (percentage of tree cover and meadow patches) were the main variables contributing to livestock kills by both species. Livestock kills were likely driven by a trade-off between livestock density and predator ecology, and the balance of this trade-off varied with scale. Risk maps revealed different hotspots for tiger and leopard kills, and analysis showed both species preferentially killed equids over other livestock types. Conclusions: Our results highlight the importance of evaluating scale when investigating the spatial attributes of livestock kills by tiger and leopard. Our findings provide guidance for reducing conflict between humans and large felids throughout the country.